79 GHz three stacked cylindrical dielectric resonator antenna array for automotive radar systems - Abderrahim Haddad; Azize Bhaij; Mousa Hussein; Mohssin Aoutoul; Mohammed El Jourmi; Elhadi Baghaz; Said Dlimi; Youssef Errami; Abdellatif Obbadi; Fadwa El Moukhtafi; Redouane Jouali (Universitas Ahmad Dahlan, 2025)
Very high gain and sharp radiation beam of an original antenna array design, made of 16 linear three stacked cylindrical dielectric resonator antennas (three ScCDRA), is proposed in this work for automotive short-range radar (SRR) applications operating at 79 GHz. Firstly, a single antenna which functions around 79 GHz and reaches a gain value up to 11.8 dB is designed with success by piling three cylindrical DRA having permittivity values, respectively, 17.9, 16.9, and 9. However, relatively near peak values, of the main and the side lobs, makes the preliminary design less efficient for vehicle radar applications. To get a radar design with enhance properties, such as lower return loss, higher gain and especially reduced radiation pattern side lobs, we proceeded with an array design of 16 linear antenna-elements (1×16). As results, the three ScCDRA array structure provides 21.3 dB as gain peak value, a very narrow angular half power beam width (HPBW) of radiation pattern of 0.7 degree at 79 GHz. Feeding network design and positions of the sixteen linear antenna-elements, within this array, have been extensively investigated to carry out an optimal design still resonating around 79 GHz with a lower S11 parameter value up to -40 dB and hilly directional characteristics of radiation diagram.